ANALISIS REDAMAN SERAT OPTIK TERHADAP PERFORMANSI SKSO MENGGUNAKAN METODE LINK POWER BUDGET (STUDI KASUS PADA LINK PADANG-BUKITTINGGI DI PT. TELKOM PADANG) - Ilham Sudrajat; Yasdinul Huda; Delsina Faiza (Universitas Negeri Padang, 2014)
Based on the survey data of optical fiber service, the communication network uses optical fiber transmission medium is not maximal yet, because there are some errors in the network, such as the percentage of Network Post Dialing Delay in system is 97.5%, that means there is 2.5% of error a delay occurs in the network when making a call. This research was conducted by analyzing the fiber attenuation of fiber-optic communication systems performance on the link Padang-Bukittinggi in PT. Telkom Padang, SKSO division which uses single mode fiber optic cable types G655. Instrument in this study is the Power Meter and OTDR JDSU MTS-6000 type. Link Power Budget method is used to determine the performance of optical fiber communication systems caused by attenuation based on the value of the received power output. Obtained results on the link Padang-Bukittinggi highest attenuation occurs in core 5 with 26.7226 dB attenuation value and cable length 115 016 km, and in core 7 with 26.1812 dB and cable length 94 462 km. This value is still below of PT. Telkom standard with 28.10352 dB for core 5. While the attenuation value at 7 cores exceeds standard attenuation values​​, with 24.18186 dB, so the performance of the core is declared bad and needs to be evaluated. From optical fiber attenuation value, result of the link power budget analysis is obtained from the calculation of the value of Rx is smaller when compared with -27 dBm the value of Rx sensitivity, it can be said the performance of optical fiber communication systems on the link in the normal state and can be used to operate because the power output can be accepted by the receiver in the device. Keywords: fiber optic cable, optical fiber attenuation, SKSO, link power budget.